The acute toxicity of Averrhoa bilimbi Linn leaves and fruits ethanolic extracts and their antidiabetic and anticoagulant activities / Nurafifah Daud - Daud, Nurafifah (2016)
Diabetes mellitus is associated with hypercoagulation by altering the clotting factor levels. Hypercoagulation may increased thrombus formation, leading to thrombosis and other cardiovascular diseases. A. bilimbi has been reported to have hypoglycemic activity. Therefore this study is attempted to investigate whether A. bilimbi could also reduced hypercoagulation following a reduction in blood glucose level. The rats were made diabetic using intraperitonial injection with alloxan monohydrate at a dose of 160 mg/kg. Acute toxicity of an ethanolic A. bilimbi leaves and fruits extract were conducted on normal rats at doses of 2000 and 5000 mg/kg in a volume of 1 ml/100 g. Glucose tolerance were studied on alloxan-diabetic rats using doses of 75, 125 and 250 mg/kg. In anticoagulant study, ethanolic extract of leaves and fruits of A. bilimbi (250 mg/kg) respectively was orally administered to both normal and diabetic Sprague Dawley rats for 14 consecutive days. After 14 days, samples of blood were then drawn and centrifuged (5000 rpm,15 min, 4°C) to obtain the plasma. Anticoagulant activity of the samples was assessed using thrombin assay and clotting time assay. Data were compared using paired sample t-test by SPSS. The present study found that an ethanolic extract of A. bilimbi leaves and fruits extract having acute toxicity that lies in the range of 2000 mg/kg < LD50 < 5000 mg/kg, regulate glucose effectively at a dose of 250 mg/kg, and possess anticoagulant activity that acted through fibrinolysis and thrombin inhibition. The strength of anticoagulant activity in descending order is heparin > A. bilimbi leaves > metformin > A. bilimbi fruits. Hepatoprotective and nephroprotective effect was also observed in liver and kidney sections of alloxandiabetic rats after treatments with A. bilimbi extract. It was a great choice to use A. bilimbi in the treatment of diabetes mellitus since it possess both antidiabetic and anticoagulant activity, as well as tissue protective effect.